Evaluation Of Hospital Information Systems (HIS) In General Hospitals Of Tehran University Of Medical Sciences (Perspective Of Physician And Nurses) - Marjan Ghazi Saeedi; Reza Safdari; Roya Sharifian; Niloofar Mohammadzadeh (Tehran University of Medical Sciences, 2014)
Background and Aim: If the evaluation is done from the perspective of users, Successful development of measures and features related to use and implementation of hospital information system and identify areas that need further consideration is to be provided. The main purpose of this study was assessment the views of physicians and nurses of hospital information system; identify the effective criteria for the use of it and their satisfaction. Materials and Methods: Present research is a descriptive cross-sectional study and was applied in public- education hospitals of Tehran University of Medical Sciences in 2012- 2013. The main tool was a questionnaire prepared by reviewing relevant literature in databases Iranmedex, Magiran, SID, PubMed, Science direct, Google scholar, and surveys by experts. In order to determine the validity, a questionnaire was distributed among 5 experts in the area of ​​information technology. After completion of the questionnaires, results were analyzed using software SPSS17. Results: Information systems in half of the hospitals surveyed from the perspective of research community have an average of 30 - 60 percent capabilities in order management. Also users in all surveyed hospitals with more than 43 % agree the ease of using hospital systems. Conclusion : User satisfaction is a guarantee for the implementation of information system. To improve the situation and move towards the ideal condition we suggest users needs in hospital information systems should be considered. Also design and system should be Compatible with the skills and knowledge of users as possible.